UNIQUE TRADITIONS OF KASHQADARYA-SURKHANDARYA BAKHSHI SCHOOL (Ta'limning zamonaviy transformatsiyasi, 2024)
Just as each Bakhshi school has its own traditions in epic performance, the Kashkadarya-Surkhandarya oasis also has its own characteristics of epic performance. The representatives of this school and the epics from their repertoire differ from other schools of epics by the features of epic performance. In this article, the unique aspects of epic performance schools, including Kashkadarya-Surkhandarya epic performance traditions, are scientifically analyzed.